2017
DOI: 10.1016/j.ajp.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Self-harm and suicide attempts in Schizophrenia

Abstract: Background The risk of suicide among persons with schizophrenia (SZ) is higher than in general population, with multiple contributory factors. We assessed the prevalence of risk of deliberate self-harm and suicide attempts, along with associated socio-demographic and clinical factors in a group of SZ outpatients (n=61) as part of a larger study on overall schizophrenia-associated risks. Aims To investigate factors associated with risk of deliberate self-harm and suicide among persons with schizophrenia. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 34 publications
2
18
1
6
Order By: Relevance
“…One-fourth of schizophrenia patients in acute wards showed self-harm and suicidal behaviors. ( 20 ) In the present study participants who underwent milieu therapy showed significantly decreased self-harm behavior compared to patients who underwent only routine therapy. In the present study milieu therapy ensured safe and secure environment by removing sharp objects from the patient environment, encouraged patient to express his negative emotions, taught safe and unsafe behavior, reinforced adaptive behavior.…”
Section: Discussionsupporting
confidence: 49%
“…One-fourth of schizophrenia patients in acute wards showed self-harm and suicidal behaviors. ( 20 ) In the present study participants who underwent milieu therapy showed significantly decreased self-harm behavior compared to patients who underwent only routine therapy. In the present study milieu therapy ensured safe and secure environment by removing sharp objects from the patient environment, encouraged patient to express his negative emotions, taught safe and unsafe behavior, reinforced adaptive behavior.…”
Section: Discussionsupporting
confidence: 49%
“… 6 , 30 The risk is highest among patients during the early stage of their illness or their first episode. 5 Most suicide attempts occur within 2 years after the first episode of psychosis, 31 , 32 and suicide-related mortality is higher among individuals recently diagnosed as having schizophrenia (ie, ≤5 years from diagnosis). 33 The higher risk of suicide compared with later stages of schizophrenia might be explained by the critical period hypothesis, which states that the primary clinical and psychosocial deterioration associated with schizophrenia occurs within the first 5 years, the critical period.…”
Section: Discussionmentioning
confidence: 99%
“…This may bias the validity of the pooled prevalence of suicide attempts across studies with different timeframes and sampling. Other than the confounding effects caused by potential recall bias and small number of studies, various factors such as more severe psychotic symptoms, impaired global functioning from onset and stigma could increase the risk of suicidal behaviours in individuals with schizophrenia (Kaplan and Harrow, 1996 ; Radomsky et al ., 1999 ; Assefa et al ., 2012 ; Jakhar et al ., 2017 ). Patients with a younger age of illness onset had a higher risk of suicide attempts, which is consistent with some (Panariello et al ., 2010 ; Vinokur et al ., 2014 ; Niehaus et al ., 2004 ), but not all studies (Popovic et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%